Experimental exploration of a mixed helium/carbon beam for online treatment monitoring in carbon ion beam therapy - Volz, Lennart; Kelleter, Laurent; Brons, Stephan; Niebuhr, Nina Isabelle; Scheloske, Stefan; Schömers, Christian; Seco, Joao (Physics in medicine and biology, 2020)
Recently, it has been proposed that a mixed helium/carbon beam could be used for online monitoring in carbon ion beam therapy. Fully stripped, the two ion species exhibit approximately the same mass/charge ratio and hence could potentially be accelerated simultaneously in a synchrotron to the same energy per nucleon. At the same energy per nucleon, helium ions have about three times the range of carbon ions, which could allow for simultaneous use of the carbon ion beam for treatment and the helium ion beam for imaging. In this work, measurements and simulations of PMMA phantoms as well as anthropomorphic phantoms irradiated sequentially with a helium ion and a carbon ion beam at equal energy per nucleon are presented. The range of the primary helium ion beam and the fragment tail of the carbon ion beam exiting the phantoms were detected using a novel range telescope made of thin plastic scintillator sheets read out by a flat-panel CMOS sensor. A 10:1 carbon to helium mixing ratio is used, generating a helium signal well above the carbon fragment background while adding little to the dose delivered to the patient. The range modulation of a narrow air gap of 1 mm thickness in the PMMA phantom that affects less than a quarter of the particles in a pencil beam were detected, demonstrating the achievable relative sensitivity of the presented method. Using two anthropomorphic pelvis phantoms it is shown that small rotations of the phantom as well as simulated bowel gas movements cause detectable changes in the helium/carbon beam exiting the phantom. The future prospects and limitations of the helium/carbon mixing as well as its technical feasibility are discussed.
Gesehen am 16.04.2020